ANALISIS PENILAIAN PERUSAHAAN DENGAN MENGGUNAKAN RASIO PROFITABILITAS DAN ECONOMIC VALUE ADDED (EVA): (Studi Kasus pada PT Alam Sutera Realty Tbk yang terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Alifia Qothrun Nada; Diah Agustina Prihastiwi (Transpublika Publisher, 2022)
This study aims to analyze the financial performance of PT Alam Sutera Realty Tbk for the period 2017-2021 by using the profitability ratio (ROI parameter) and the economic value added (EVA) method. The type of research used is descriptive research with a quantitative approach. The object of this research is a company listed on the IDX, PT Alam Sutera Realty Tbk for the period 2017-2021. The results indicate that the results of measuring financial performance using profitability ratios with ROI parameters as a whole can be said to be good because the average value is positive, which is 2.35%. While the measurement results using the EVA method show a positive average value, which is Rp. 12.074.826-, which means the company has succeeded in creating added value, although in certain years it has decreased.